Meta Analisis Studi Kelas Menengah Muslim di Indonesia - M. Yusuf; Afrizal Afrizal; Bob Alfiandi (Indonesian Center for Religion and Society Studies (InTReSt), 2022)
The emergence of the Islamic populism movement marked by the